Modelo de perfusao pulmonar isolada em ratos com metastases pulmonares de sarcoma - Schneider, Airton (1991)
Aproximately 4500 new cases of sarcoma are reported in USA each year. Seventy five percent will develop lung metastases and at majority which the only site. The best resulta of surgical treatment do not excced 32% of the cases. The use of adjuvant chemotherapy has reduced but not eliminated the incidence of pulmonary metastases. The perfusion of one organ with more drug and without systemic effects of chemotherapy can change the natural history of thia diaease. We present the result of the first phase which ia to set up successfully the model of perfusion and of the aecond phase, which ia to develop the pulmonary sarcoma metaatases. We were able to perfuse the left lung of 14 rata and to follow them up, at least for 10 days. The overall mortal i ty r ate was 28,5%. Wi th improvement of the technique, we had 10% of mortality. In the second phase, we were able to produce aarcoma metastases in 32 days, following intravenous injection of sarcoma cella auspenaion. Therefore, the first lung perfusion model in successfully. phase, to implement the single the rat, has been accomplished The aecond phase ahowed us that the pulmonary aarcoma metastases model ia confirmed. The CT scan can be used instead of sacrificing the animais to follow up the metastases.